PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE TERHADAP KEMAMPUAN BERKOMUNIKASI SISWA PADA MATERI ORGANISASI KEHIDUPAN (Penelitian pada Siswa Kelas VII SMPN 1 Tanggeung Cianjur) - Rena Purnamawanti; Sri Hartati; Sumiyati Saádah (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2015)
On learning activities in the class, teachers are faced with the reality of individual differences in ability. One of the causes that problem are students communication ability and the the teacher must determine the exact learning model to be used based on premilery study at SMPN 1 Tanggeung Cianjur, the ability of students communication at seventh class at material of organisasi kehidupan in the previous year are relatively low. Beside it, the cooperatif learning model tipe inside outside circle on the subject of Biologi has never been used. The purpuse of this research are for finding out the feasibility of study , to find out the students communication with or without learning model, analyzing the effect of learning model and knowing students respon on learning after using learning cooperatif model tipe inside outside circle of the organiasi kehidupan material. The research used quasi experiment method with nonequivalent control group design and the researcer took of the sample fromtwo classes with purposive sample technique, the instrument that was used was observation sheets, questionnaire, pretest and posttest in the form of twenty multiple choice questions that had been previously tasted. From the analysis that the feasibility study had increased, the activity of the teachcer in experiment class by 93,3 % was excellent categorized and control class 97% was excellent categorized too. The students communication in experiment class in average scores of pretest were 50,31, posttest 70,94 and N-gain 0,42 in medium categorized. Retrieved Zhitung 2,28 with the significant 5%, while the Ztabel1,65. Because Zhitung>Ztabel it can be concluded that Ho was rejected dan Ha was accepted. It’s mean that there was an effect of kooperatif learning model tipe inside out side circle on communication students skill at organisasi kehidupan materials. The students respon on learning using kooperatif learning model tipe inside outside circle had responded excelent with the average 83,05% with strong kualification.